(maktabah) ØªØ£Ø«ÙŠØ± Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØÙØ± Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù„Ù„Ø·Ø§Ù„Ø¨Ø§ Ù…Ø¬Ù„ÙŠØ³ Ø³ÙˆØ±ÙˆÙƒØ§Ù† ÙƒØªØ§Ø¨ Ù„Ù„Ø·Ø§Ù„Ø¨Ø§Øª - anyes latifatul insyaniah; anis fatussholehah (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
This research is aimed at three main things, namely: to know the implementation of "drill method", Qira'ah ability and the effect of "drill method" on the improvement of Maharah Qira'ah students of maktabah. class 4 ula Darussalam Blokagung Tegalsari Islamic Boarding School Banyuwangi 2018/2019 Learning Year. This research uses quantitative descriptive method with product moment technique. Methods of data collection using observation techniques, interviews, questionnaires and documentation. While the sample in this study was 40 students of class 4 ula maktabah. And the results of the research are (1) the implementation of the drill method of the maktabah santri has a very good value (2) the increase in maharah qira'ah of the maktabah santri has a fairly good value (3) There is a significant positive effect with a strong relationship between the drill method and the increase in maharah. qira'ah santri maktabah grade 4 ula pondok pesantren darussalam blokagung tegalsari banyuwangi in 2018/2019 learning year. The value of the effect of variable X on variable Y is 47.80% and there are still 52.2% other things that affect variable Y.